El carácter judicial de los letrados de la administración de justicia (Acta Judicial Journal, 2021)
This present work constitutes a sort of vital epitome of what the author considers was, is and should be the figure of the Legal Counsel to the Administration of Justice. Its new configuration, with the legal reforms initiated in the year 2003, meant a true transmutation of the same. They have turned him into a relevant actor in the judicial scene. This leading role, in a scenario used to having the lights focused on a single office, immediately aroused misgivings. First in the doctrine, then in the jurisprudence and, finally, in the Constitutional Court. Fears that are based on two pillars: a) a closed and narrow conception of the concept of jurisdiction; b) the organic integration of the Judicial Lawyers in the Ministry of Justice. It is possible to dispel these fears. In this task, we will draw on the same sources from which they arise: a large part of the doctrine, the jurisprudence and judgments of the Constitutional Court. The last part of the work is devoted to formulating conclusions and proposals. With them we seal the position of the Lawyers of the Administration of Justice in its natural ecosystem: the Courts and Tribunals, of which they are an essential part.
Keywords: Lawyer of the Administration of Justice, Jurisdiction, Judicial and digital public faith, Documentation and custody, Independence and legality